Dampak Financial Influencer dan Fear of Missing Out terhadap Pengalaman Investasi Aset Kripto pada Investor Generasi Z - Agasi, Muhamad Rafi; Hermawan, Adam; Purwaamijaya, Btari Mariska (Riviera Publishing, 2025)
The increasing number of young crypto investors in Indonesia has not been matched by adequate financial literacy. This study aims to analyze the impact of Financial Influencers and Fear of Missing Out (FOMO) on the experience of investing in crypto assets, with financial literacy as a moderating variable in Generation Z in Indonesia. The research approach uses a quantitative correlation method with Structural Equation Modeling (SEM) analysis techniques based on Partial Least Squares (SmartPLS 4.0). Data were obtained from 192 respondents aged 17–29 who actively invest in crypto assets through an online survey. The results show that financial literacy has a positive and significant effect on investment experience (? = 0.536; p < 0.001), while Financial Influencers (p = 0.913) and FOMO (p = 0.468) have no significant effect on financial literacy or investment experience. The R² value of 0.303 indicates that the research variables explain 30.3% of the variation in Generation Z investment behavior. This finding confirms that cognitive factors, especially financial literacy, are more dominant than social and emotional factors in shaping digital investment behavior. The results of this study strengthen the Behavioral Finance Theory and emphasize the importance of strengthening financial education for the younger generation to improve analytical skills and rational investment decision-making. Furthermore, the findings offer practical implications for the development of more effective financial education strategies, as well as theoretical contributions that deepen the understanding of determinants influencing digital investment behavior among young investors.